2012
DOI: 10.1016/j.conb.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale analysis of structural synaptic plasticity

Abstract: In the 1950’s, transmission electron microscopy was first used to reveal the diversity in synaptic structure and composition in the central nervous system [1;2]. Since then, visualization and reconstruction of serial thin sections have provided three-dimensional contexts in which to understand how synapses are modified with plasticity, learning, and sensory input [3–17]. Three-dimensional reconstruction from serial section electron microscopy (ssEM) has proven invaluable for the comprehensive analysis of struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 81 publications
3
79
0
1
Order By: Relevance
“…The accumulation of oxidative damage in the CNS has been shown to result in decreased efficiency of LTP (Lynch, 2004;Serrano and Klann, 2004). The maintenance of LTP also involves the growth of the synaptic membrane of excitatory synapses (Bourne and Harris, 2012), suggesting that LTP may be impaired in Neil3 À/À mice. Activation of GABA A receptors in the hippocampus was previously shown to have an anxiolytic effect (Engin and Treit, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of oxidative damage in the CNS has been shown to result in decreased efficiency of LTP (Lynch, 2004;Serrano and Klann, 2004). The maintenance of LTP also involves the growth of the synaptic membrane of excitatory synapses (Bourne and Harris, 2012), suggesting that LTP may be impaired in Neil3 À/À mice. Activation of GABA A receptors in the hippocampus was previously shown to have an anxiolytic effect (Engin and Treit, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies showed that TBS causes rapid (Ͻ2 min), integrin-dependent formation of subsynaptic actin filaments (Kramár et al, 2006) that are stabilized by processes reflecting a second signaling cascade over the following 5-10 min (Rex et al, 2009). It is possible that the integrin recovery is needed to anchor the newly formed actin networks to the extracellular matrix, and thereby to maintain the structural modifications of synapses that accompany and stabilize LTP (Chen et al, 2007(Chen et al, , 2010bYang et al, 2008;Bourne and Harris, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Spine shape and number are not necessarily dependable predictors of synapse size, location, or composition (Fiala et al 1998;Toni et al 2007;Bock et al 2011;Shu et al 2011). A more reliable assessment requires nanoscale 3D reconstruction from serial section EM, which allows one to understand how changes in structure affect synaptic connectivity and function (Harlow et al 2001;Denk and Horstmann 2004;Coggan et al 2005;Toni et al 2007;Lichtman and Sanes 2008;Meinertzhagen et al 2009;Cardona et al 2010;Mishchenko et al 2010;Ostroff et al 2010;Bock et al 2011;Helmstaedter et al 2011;Bourne and Harris 2012;Cardona 2013;Lu et al 2013;Wilke et al 2013). Live imaging with two-photon microscopy also has revealed rapid, activity-dependent turnover of spines, which is common in the neocortex (and, presumably, the hippocampus) during development, but as an animal matures, more of the spines begin to stabilize Holtmaat and Svoboda 2009).…”
Section: Structural Components Of Synaptic Plasticitymentioning
confidence: 99%